The landscape institute - Nygren, Tea (My University, 2025)
This master thesis explores the role of the landscape as a secondary entity to total urbanisation. The aim of the thesis is to explore how we can reimagine supporting areas, with the ambition to foster a deeper understanding of landscapes, urbanisation and people. The thesis intends to explore how, in future societal development, we can oppose the landscape as a prime economic asset and in contrast to a current static state, reimagine supply areas as sites of progress. Contextualised in Umeå river in northern Sweden, the thesis conducts a narrative divided in five phases; background, site, manifesto, strategies and The landscape institute. Outlined by a theoretical framework, this narrative unfolds a discourse that raises the following research questions; How can architecture create conditions of care for nature in future societal de velopment? How can a physical space be designed to communicate, restore and enrich the landscape, rather than exploit it? What follows is an investigation where prototyping serves as a mediator between the positioning of the thesis, the manifesto, and the design outcome, The Landscape Institute. The result is a project in two senses; an architectural artefact as well as a campaign. The landscape institute becomes a method to frame a need of a site and empower further questioning of human positioning in the landscape. The thesis highlights a future where we collectively transcend our superiority to land, and where architecture becomes a tool for communication, restoration and enrichment.